'An unrivalled brass Lectorium': the Cloisters lectern and the Gothic Revival in England. (2020) - Brine, Douglas
Abstract : The Cloisters, the Metropolitan Museum of Art's outpost for medieval art, houses an elaborate brass eagle lectern made in the Netherlands in c. 1500. Purchased in 1968 from Oscott College, it had previously been in St Chad's Cathedral, Birmingham, a key site of the Gothic Revival in England. This article examines the Cloisters lectern's sojourn in Victorian Britain, beginning with its arrival on the London art market and publication in Specimens of Ancient Furniture in the 1830s. The main focus is its subsequent association with the architect, designer and theorist A. W. N. Pugin, who designed and furnished St Chad's as Britain's first Catholic cathedral since the Reformation. The lectern helped to define the Catholic identity of Pugin's vision of the revived Gothic style. It also influenced his own designs for metalwork, reflecting his keen interest in Netherlandish brass sculpture.